The social environment of talent development in youth sport - Henriksen, Kristoffer; Stambulova, Natalia (Frontiers in Sports and Active Living, 2023)
During the last decade, talent identification and development research that favored an individual perspective was complemented by a focus on young athletes’ social environments termed athletic talent development environments (ATDEs). Two major lines of research created a foundation for an ecological vision of talent development as the mutual accommodation between athletes and their ATDEs, and of career development as an athlete’s journey through various athletic and non-athletic environments. The Talent Development Environment Questionnaire allowed to quantitatively screen athletes’ environments, while the holistic ecological approach (HEA) promoted in-depth qualitative case studies of ATDEs. In this chapter we focus mainly on the HEA including: (a) two models that combine to illustrate an ATDE, (b) a summary of empirical case studies of successful environments in various sports and countries culminating in a set of shared features of ATDEs that promote athletes’ wellbeing, athletic, and personal development, (c) an overview of recent trends within HEA (e.g., interorganizational collaboration in talent development), and (d) recommendations for coaches and sport psychology consultants emphasizing the importance of integrating efforts across the whole environment and building strong and coherent organizational cultures. In the discussion we elaborate on developing the HEA discourse and future challenges for researchers and practitioners.